RELASI ANTARA IDEOLOGI DENGAN MEDIA MASSA - Abdul Basit (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2007)
The progress of mass media is influenced by the development of social theories. One interesting case to be discussed is the relation between ideology and mass media.There are three main groups which have different views on the relation between ideology and mass media. Marxist States that mass media is an institution which can be used to socialize false ideology built by borjuis class. Another group, the liberal pluralist, States that mass media is an institution which is free from interventions of State, political parties, and other repressing groups so that ideology has no relationship with mass media. The third, the critical group, States that texts produced by mass media is not free from any conflicts and interests. This group tries to rebuild the relationship between ideology and mass media.However, the ideology developed by this group is not an flght ideology or false awareness, but an ideology emphasizing on the articulation of meaning or ideology which functions as a discussion and logical social process.